CompTIA A+ 220-801 and 220-802 LiveLessons (video training) - Graham, Robin Donald; Smith, Beth.; Safari eBooks ([S.l.] : Addison-Wesley, 2012)
"The brand-new CompTIA A+ LiveLessons is the ultimate electronic study package for today's A+ candidate! CompTIA A+ LiveLessons offers more than 13 hours of expert, step-by-step video walkthroughs covering exam objectives for both A+ exams. Just watch, master, and review the new A+ objectives. This product provides comprehensive preparation for both new CompTIA A+ exams: A+ 220-801, A+ 220-802.""--Resource description page.
Title from resource description page (viewed Mar. 5, 2013).
Produced by Instructional Scenarios.
Presenters, Robin Donald Graham, Beth Smith.
Keywords: Electronic data processing personnel -- Certification; Computer technicians -- Certification; Microcomputers -- Maintenance and repair -- Examinations -- Study guides; Computing Technology Industry Association -- Examinations -- Study guides; Electronic books